Volunteer translators as ‘committed individuals’ or ‘providers of free labor’? The discursive construction of ‘volunteer translators’ in a commercial online learning platform translation controversy - Kang, Ji Hae; Hong, Jung Wook (Meta (Canada), 2020)
This study explores the ways in which volunteer translation in a commercial context is discursively constructed. It focuses on volunteer translation at Coursera, one of the world’s largest MOOC providers, and its volunteer translator community, launched in 2014 to offer online learning in multiple languages. This move to mobilize volunteer translators by Coursera, a for-profit company, became controversial as different parties voiced distinct opinions regarding a commercial company’s recruitment of volunteer translators. Using the Critical Discourse Analysis (CDA) framework and drawing on the notion of digital labor, this paper argues that volunteer translation is described by Coursera mostly in terms of a mission and a learner-initiated and community-building activity. This contrasts with the view of many social critics who tend to emphasize profit-making strategies, labor exploitation, and the degradation of the translation profession in their discursive construction of volunteer translation. This study shows that Coursera’s foregrounding of a moral rationale and of philanthropic and non-profit discourses blurs the boundary between for-profit and non-profit contexts and does the ideological work
Keywords: Crowdsourcing; Digital labour; Digital platform; Ethics; MOOC; Volunteer translation